Genome-Wide Identification of MicroRNAs and Their Targets in the Leaves and Fruits of Eucommia ulmoides Using High-Throughput Sequencing - Wang, Lin; Du, Hongyan; Wuyun, Ta-na (Frontiers in Plant Science, 2016)
MicroRNAs (miRNAs), a group of endogenous small non-coding RNAs, play important roles in plant growth, development, and stress response processes. Eucommia ulmoides Oliver (hardy rubber tree) is one of the few woody plants capable of producing trans-1, 4-polyisoprene (TPI), also known as Eu-rubber, which has been utilized as an industrial raw material and is extensively cultivated in China. However, the mechanism of TPI biosynthesis has not been identified in E. ulmoides. To characterize small RNAs and their targets with potential biological roles involved in the TPI biosynthesis in E. ulmoides, in the present study, eight small RNA libraries were constructed and sequenced from young and mature leaves and fruits of E. ulmoides. Further analysis identified 34 conserved miRNAs belonging to 20 families (two unclassified families), and 115 novel miRNAs seemed to be specific to E. ulmoides. Among these miRNAs, fourteen conserved miRNAs and 49 novel miRNAs were significantly differentially expressed and identified as Eu-rubber accumulation related miRNAs. Based on the E. ulmoides genomic data, 202 and 306 potential target genes were predicted for 33 conserved and 94 novel miRNAs, respectively; the predicted targets are mostly transcription factors and functional genes, which were enriched in metabolic pathways and biosynthesis of secondary metabolites. Noticeably, based on the expression patterns of miRNAs and their target genes in combination with the Eu-rubber accumulation, the negative correlation of expression of six miRNAs (Eu-miR14, Eu-miR91, miR162a, miR166a, miR172c, and miR396a) and their predicted targets serving as potential regulators in Eu-rubber accumulation. This study is the first to detect conserved and novel miRNAs and their potential targets in E. ulmoides and identify several candidate genes potentially controlling rubber accumulation, and thus provide molecular evidence for understanding the roles of miRNAs in regulating the TPI biosynthesis in E. ulmoides.